2016
DOI: 10.1177/1557988316637645
|View full text |Cite
|
Sign up to set email alerts
|

Conflict in Men’s Experiences With Antidepressants

Abstract: While men’s experiences of depression and help seeking are known to be shaped by gender, there is little research which examines their experience of using antidepressants to treat this. This study is based on in-depth, narrative-style interviews with 20 New Zealand men who had used antidepressants. The analysis identified a number of areas of conflict in the men’s accounts of using this medication. Conflict centered on the way taking antidepressants was seen as undermining personal control while also allowing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 65 publications
7
15
0
Order By: Relevance
“…Perceived distortions in sense of self and exercise of agency, associated with a sense of altered reality and dissociated embodiment, attributed by users as a side effect of the antidepressant medication, are well reported in existing research (Read et al, 2014;Gibson et al, 2018), and our participants also voiced these concerns. For Tom, one of the most pronounced negative effects attributed to the medication was a sense of unreality and disembodiment: This concern is consistent with the findings from the Gibson et al (2018) study, in which the men reported being particularly concerned with loss of vitality and sensory engagement, rather than loss of empathy or concern for others, which research has suggested may be more often reported as a concern for women (Fullagar and O'Brien, 2012). Harry reports a numb "dream like state" when he first started taking the medications, whilst George reports "feeling constantly flat", which impacts on his ability to write music, an identity defining occupation linked with enjoyment:…”
Section: Unreality and Disembodimentsupporting
confidence: 71%
See 1 more Smart Citation
“…Perceived distortions in sense of self and exercise of agency, associated with a sense of altered reality and dissociated embodiment, attributed by users as a side effect of the antidepressant medication, are well reported in existing research (Read et al, 2014;Gibson et al, 2018), and our participants also voiced these concerns. For Tom, one of the most pronounced negative effects attributed to the medication was a sense of unreality and disembodiment: This concern is consistent with the findings from the Gibson et al (2018) study, in which the men reported being particularly concerned with loss of vitality and sensory engagement, rather than loss of empathy or concern for others, which research has suggested may be more often reported as a concern for women (Fullagar and O'Brien, 2012). Harry reports a numb "dream like state" when he first started taking the medications, whilst George reports "feeling constantly flat", which impacts on his ability to write music, an identity defining occupation linked with enjoyment:…”
Section: Unreality and Disembodimentsupporting
confidence: 71%
“…"you feel like a sort of porn star, you can go for hours you know [laughs]" (Samuel) Yet despite trying to reframe the situation, participants were unable to fully normalize this new form of embodiment, and it removed enjoyment of sexual activity, which previous research has suggested may become a source of distress in itself and further increase feelings of depression (Gibson et al, 2018).…”
Section: Unreality and Disembodimentmentioning
confidence: 99%
“…There is limited knowledge about men's views of taking antidepressants. Studies suggest findings are similar to non-gender specific studies, although hegemonic masculinity is influential for some aspects 20,54 . Some men felt taking antidepressants compromised hegemonic masculine traits such as control and autonomy 54 .…”
supporting
confidence: 61%
“…Studies suggest findings are similar to non-gender specific studies, although hegemonic masculinity is influential for some aspects 20,54 . Some men felt taking antidepressants compromised hegemonic masculine traits such as control and autonomy 54 . These traits are especially valued by men 55,56 .…”
supporting
confidence: 61%
“…In addition to the impact of expectations regarding male roles on help-seeking behavior, studies revealed positive as well as negative experiences of (mental) health service use among men with depression. A recent qualitative study referred to conflicts that men experienced in relation to antidepressant use (9). On the one hand, medication was perceived as a way in which men asserted their control over difficulties; on the other hand, antidepressants were seen as an obstacle to emotional and physical vitality, for example by undermining sexual function.…”
Section: Introductionmentioning
confidence: 99%